Now It’s My Time! Black Girls Finding Space and Place in Comic Books - Grace D. Gipson (Arts, 2023)
This essay examines how Black girl narratives are finding and making space and place in the arena of comic books and television. With the rise in Black girl (super)hero protagonists on the comic book pages and adapted television shows, it is essential to explore the significance of their rising inclusion, visibility, and popularity and understand how they contribute to the discourse surrounding the next generation of heroes. Guided by an Afrofuturist, Black feminist, and intersectional framework, I discuss the progressive possibilities of popular media culture in depicting Black girlhood and adolescence. In Marvel Comics’ “RiRi Williams/Ironheart”, DC Comics’ “Naomi McDuffie”, and Boom! Studios’ “Eve”, these possibilities are evident. Blending aspects of adventure, fantasy, sci-fi, and STEM, each character offers fictional insight into the lived experiences of Black girl youth from historical, aesthetic, and expressive perspectives. Moreover, as talented and adventurous characters, their storylines, whether on the comic book pages or the television screen, reveal a necessary change to the landscape of popular media culture.